Assessing the role of temperature and air pollution in exacerbating childhood asthma in Cape Town, South Africa - Phakisi, Tshepo Kingsley (Department of Public Health and Family Medicine, 2023)
Childhood asthma is one of the most common chronic diseases worldwide, including in South Africa. There has been substantial evidence on the role of air pollution in asthma exacerbation but limited research on the role of climate change and how the interaction between climate change and air pollution is affecting childhood asthma, specifically in low and middle-income countries (LMICs). Temperature changes can be used as an effect of climate change to investigate the association between climate change, air pollution and childhood asthma. This study, therefore, used a case study approach aimed at examining the interaction between air pollution and temperature in exacerbating childhood asthma focusing on clinical data obtained from Red Cross War Memorial Children's Hospital, air quality data (City of Cape Town) and temperature data (South African Weather Services) for Cape Town, South Africa for three study years (2009, 2014 and 2019). The protocol (Part A) of the mini dissertation describes childhood asthma literature globally and in LMICs and specifically in South Africa. It also discusses the increasing incidences and prevalence of the disease and possible causes such as air pollution and climate change. Furthermore, it discusses the vulnerability of children to the exposure of interest, being air pollution (PM2.5, PM10, NO2 and O3) and climate change (i.e., temperature). Subsequently, the development of air quality standards is discussed, specifically concerning whether they consider the specific children's vulnerability to exposures. The protocol then describes the study population and methodologies for conducting this study. The journal ready article (Part B) presents the findings of the study. Spearman's correlation was used to measure the degree of association between temperature variables and air pollutants. The results indicated that diurnal temperature was associated with PM2.5 (r=0.579: p< 0.01) and PM10 (r=0.505: p< 0.01). A Poisson regression analysis was applied to evaluate the relationship between asthma exacerbation with air pollutants and temperature variables. In a univariate analysis there was a statistically significant relationship between asthma exacerbation and diurnal temperature for 2019, IRR=0.98 (95% CI,0.97 – 0.99) p< 0.05, maximum temperature 2014, IRR=0.99(95% CI, 0.98 - 1.00) p< 0.05 and for 2019, IRR=0.98(95% CI, 0.97 - 0.99) p< 0.01, average temperature 2014, IRR=0.99(95% CI, 0.98 - 1.00) p< 0.05 and for 2019, IRR=0.98(95% CI, 0.97 - 0.99) p< 0.01. Using a multivariate analysis there v of 110 was no significant relationship between childhood asthma exacerbation and air pollutants (PM10, NO2 and O3) except for PM2.5 IRR=0.12(95% CI, 0.01 - 0.81) p< 0.05. Diurnal temperature statistically significant childhood asthma predictor for 2009, IRR=1.02(95% CI, 1.00 - 1.05) p< 0.05 and for 2014, IRR=0.97(95% CI, 0.96 - 0.99) p< 0.01. Temperature increase, therefore, seems to be related to asthma exacerbation. More research is needed on the relationship between diurnal temperature, childhood asthma, and air pollutants to inform adaptation strategies. The findings of this study are important for the development of climate change and health adaptation and prevention strategies in South Africa, particularly in relation to heat adaptation. These findings are also relevant for the development of air quality guidelines and guidelines to address children, as the most vulnerable population to environmental health exposures. The appendices (Part C) present the analyses that were not included in the protocol (Part A) and article (Part B). These also include documents relating to the study such as ethics approval and permission to conduct research by different entities.